2020
DOI: 10.1055/a-1213-5761
|View full text |Cite
|
Sign up to set email alerts
|

ESGE and ESGENA Position Statement on gastrointestinal endoscopy and COVID-19: An update on guidance during the post-lockdown phase and selected results from a membership survey

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 24 publications
(41 reference statements)
1
77
0
7
Order By: Relevance
“…Guidance was required urgently for endoscopic procedures at peak infection, particularly in light of the information on gastrointestinal viral shedding, and only emergency endoscopic procedures were performed with full PPE utilised. Thankfully, updated advice following surveys of clinicians have been produced to guide endoscopists in the post-lockdown period [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Guidance was required urgently for endoscopic procedures at peak infection, particularly in light of the information on gastrointestinal viral shedding, and only emergency endoscopic procedures were performed with full PPE utilised. Thankfully, updated advice following surveys of clinicians have been produced to guide endoscopists in the post-lockdown period [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…A European survey reported that contact for patients after 7–14 days from endoscopy to inquire about COVID-19 symptoms was done only 28.3% of the time. 29 …”
Section: Discussionmentioning
confidence: 99%
“…As the COVID-19 pandemic continues to unfold, and with an increased pressure of re-opening endoscopy wards likely to result in an increased number of procedures in COVID-19 patients, 24 it is paramount to continue providing safe and effective treatment, with the aim of minimizing risks to patients and healthcare workers alike. Prospective study cohorts, including a wide variety of procedures performed during the pandemic (including COVID-19 confirmed, suspected and negative patients) could help assess the impact of individual factors such as the perceived risk of contamination and limitations of cumbersome PPE on the technical outcome of the procedures, helping to further adapt our practice in response to these new challenges facing the endoscopist.…”
Section: Discussionmentioning
confidence: 99%